Torque-compensation for energy-efficient motion of robotic limbs in a stance - Yun, Junghwan; Yi, Hak; Lee, Sangryong (Journal of mechanical science and technology, 2018)
This paper addresses a new variable stiffness actuator (VSA) of a walking robot in a stance that can actively regulate a spring preload through correlation between spring reaction forces and joint variables. Here, VSA aims to realize energy-efficient stance motion of robotic limbs system from changing working conditions of a walking robot. Compared to conventional spring-loaded structures, it can effectively control both a spring stiffness and a spring-clamping configuration on humanoid’s lower body responding on uncertainties. ADAMS / MATLAB co-simulation system and experiments on the proposed VSA system as an active torque compensator are investigated for realizing energy-efficient motion in a robot’s stance.